PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL MELALUI KEGIATAN EKSTRAKURIKULER KARAWITAN PADA SISWA SDN SUMUR WELUT III/440 SURABAYA - Faradiba Faisal, Rizqita; Irianto, Apri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is a strategic effort to shape a virtuous younger generation amid globalization, which threatens the survival of local wisdom values. This study aims to analyze the implementation of the karawitan (traditional gamelan music) extracurricular activity as a means of local-wisdom-based character education and to identify the character values developed among students at SDN Sumur Welut III Surabaya. The study draws on Thomas Lickona's theory of character education, encompassing moral knowing, moral feeling, and moral action, combined with theories of local wisdom and karawitan as a medium for character formation. A qualitative approach with a descriptive, case-study design was employed. Data were collected through interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings indicate that the karawitan extracurricular activity was implemented systematically and fostered values of religiosity, discipline, responsibility, cooperation, tolerance, and cultural pride through habituation in every practice session. However, the program still faces limited practice time and the absence of a structured character curriculum and evaluation instrument. It is concluded that the karawitan extracurricular activity is effective as a medium for local-wisdom-based character education, although its management requires more systematic strengthening.